1980
DOI: 10.1163/22941932-90000702
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Distribution of Radial Resin Canals in Larix Leptolepis Gord.

Abstract: There are about one to two radial resin canals per square millimeter in the tangential section of the late wood of each annual ring within a trunk in Larix leptolepis Gord. The diameter of radial resin canals is about 25 ).1m. In the annual ring in which there are typical traumatic resin canals in the early wood, the number of radial resin canals in the late wood is larger than that in the normal annual ring which was formed in the previous year, and it was sometimes observed that two closely spaced uniseriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…All surveyed fusiform rays (>50), without exception, contained a radial resin canal. Takizawa et al (1980) investigated the distribution of radial resin canals in Larix leptolepis Gord., and reported that there were 1 to 2 radial resin canals per square millimeter in the tangential section of the latewood of each annual ring. In this study, we found that the average number in P. densiflora was 0.76/mm 2 .…”
Section: Appearance and Frequency Of Radial Resin Canalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All surveyed fusiform rays (>50), without exception, contained a radial resin canal. Takizawa et al (1980) investigated the distribution of radial resin canals in Larix leptolepis Gord., and reported that there were 1 to 2 radial resin canals per square millimeter in the tangential section of the latewood of each annual ring. In this study, we found that the average number in P. densiflora was 0.76/mm 2 .…”
Section: Appearance and Frequency Of Radial Resin Canalsmentioning
confidence: 99%
“…Resin canals are a common feature in some coniferous trees, and members of the Pinaceae were classified in accordance with this feature by Jeffrey in 1905 (Bannan 1936). Further, in the genus Pinus, both axial and radial resin canals appear as normal features of the wood, and because of their importance in wood technology and resin extraction, their formation and anatomical features have been studied by many investigators (Bannan 1933(Bannan , 1936Chattaway 1951;Mergen & Echols 1955;Takizawa et al 1980;Nanko et al 1984;Kuroda 1986;Werker & Fahn 1969;Yamanaka 1989). The resin canals are surrounded by a layer of thin-walled, unlignified secretory cells which are termed epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, biseriate rays which result from the fusion of two uniseriate rays such as shown in Figure 21 have not been described previously. Takizawa et al (1980) sometimes observed that in Larix leptolepis within one growth period two closely spaced uniseriate rays became a multiseriate one containing a radial resin canal. The frequency of occurrence of such biseriate rays as shown in Figure 21 was not detennined in the present study.…”
Section: Abnormal Raysmentioning
confidence: 99%